Treated tropical wood sawdust-polypropylene polymer composite : mechanical and morphological study - Idrus, M.A.M.M; Hamdan, S.; Islam, M.S. (Scientific Resarch, 2011)
In this research, composites based on treated tropical sawdust and polypropylene (PP) were prepared using hot press molding machine. Raw sawdust was chemically treated with monomer, 2 - ethylhexyl methacrylate in order to improve the mechanical properties of the composites. The influence of the chemically treated sawdust on the physical and mechanical properties of sawdust-PP composites were investigated at various loading level from 10 wt.% up to 30 wt.%. Results indicate that the mechanical properties of the chemically treated sawdust–PP composites were found to be higher than those of the raw ones respectively. The surface morphology obtained from scanning electron microscopy (SEM) showed that raw sawdust–PP composites possess surface roughness and weak interfacial adhesion between the matrix and the filler while the chemically treated one showed improved filler–matrix interaction. This indicates that better dispersion of the filler with the PP matrix has occurred upon chemical treatment of the filler. Water absorption tests showed that composites prepared from the chemically treated sawdust absorb lower amount of water compared to the ones prepared from raw sawdust, suggesting that hydrophilic nature of the cellulose in the sawdust has significantly decreased upon chemical treatment.